Strategi Penguatan Literasi Digital untuk Meningkatkan Mutu Pembelajaran di MTSN 2 Kabupaten Kediri - MUFTI DWI SURYANSYAH; Siti Ma’rifatul Hasanah (Kelola: Jurnal Manajemen Pendidikan, 2024)
Digital literacy is an important skill in today's digital era. Digital literacy in education is a tool that helps improve the achievement of learner competencies. With digital literacy, learners can utilize technology as a tool to meet academic needs and in everyday life. Achieving digital literacy competency goals requires better efforts from teachers in choosing and implementing learning strategies, methods, and media that are in accordance with these competencies. However, the lack of attention to the development of digital literacy is a problem in the midst of people's lives. As well as the demands of the Industrial Revolution 4.0, which requires people to be good at digital literacy in everyday life. This study aims to improve the quality of learning at MTsN 2 Kediri Regency with a strategy to strengthen digital literacy. The approach and type of research used are descriptive-qualitative with triangulation methods through observation, interviews, and documentation. The data analysis technique used by the researcher is the analysis of the Miles and Huberman model. The results showed that the strategy of strengthening digital literacy begins with goal planning, policy analysis, methods, resources, strategies, and socialization. Implementation is done through various media and technology, and evaluation is done by looking at the achievement of goals, monitoring, and follow-up. The follow-up is to increase the use of multimedia, mastery of information technology, and motivation of students to strengthen digital literacy skills.